Producción de carne en diferentes grupos raciales de bovinos - Peralta Martínez, Armando (CATIE, Turrialba (Costa Rica) UCR, San José (Costa Rica), 2014)
Tesis (Mag. Sc.) -- CATIE, Turrialba (Costa Rica) -- UCR, San José (Costa Rica), 1977